Analytical – Comparative Study of Some Kinematical Variables Of Jump Shot and Shooting in Youth Basketball Players - Waleed, Omar; Hamed, Huda (Journal of Physical Education, 2017)
The importance of the research lies in identifying some kinematical variables and comparing some of these variables for scoring from the side and from standing position. The problem of the research lies in jump shooting from the side compared to standing scoring. The research aimed at identifying the values of some kinematical variables of standing shooting and side jump shooting youth basketball as well as making comparisons between kinematical variables for the two types of shooting in basketball. The researchers hypothesized significant statistical differences between standing shooting and side jump shooting in youth basketball. They also used the descriptive method. The subjects were (12) tested free shot, jump shot, etc. the data was collected and treated using SPSS to conclude and recommend making similar researches on other age groups, as well as paying attention to the preparation phase for shooting success